The journey of patients with diffuse large B-cell lymphoma: from symptoms to diagnosis - Vodicka, Prokop; Masar, Michal; Benesova, Katerina; Koren, Jan; Klener, Pavel; Polgarova, Kamila; Galko, Jan; Jaksa, Radek; Campr, Vit; Dlouha, Jitka; Hrabetova, Sarka; Blahovcova, Petra; et al. (Leukemia & lymphoma, 2025)
Symptoms of lymphomas include peripheral lymphadenopathy, B-symptoms, and other organ-specific symptoms; however, data on initial symptoms incidence in diffuse large B-cell lymphoma (DLBCL) remain limited. We aimed to investigate real-world patterns of initial DLBCL symptoms, correlating them with baseline characteristics and symptom onset-to-diagnosis interval. Patients with DLBCL diagnosed between 2010 and 2021 receiving R-CHOP were screened. 706 individuals with reported initial symptoms were analyzed. 682 (97%) patients had documented symptoms; remaining 24 patients (3%) had incidental findings discovered during examinations for unrelated reasons. Abdominal/gastrointestinal complaints were the most prevalent symptoms (26%), followed by peripheral lymphadenopathy (22%), and B-symptoms (13%). The median symptom-to-diagnosis interval was 10 weeks. Peripheral lymphadenopathy and testicular tumors correlated with low-risk characteristics, with testicular DLBCL featuring a shorter symptom-to-diagnosis interval. Limb pain/swelling and back pain were associated with high-risk characteristics and prolonged symptom-to-diagnosis interval. This analysis enhances our understanding of DLBCL symptomatology, aiding in timely recognition and management.
Keywords: Non-Hodgkin lymphoma; Vincristine; Humans; extranodal lymphoma; lidé středního věku; doxorubicin; Aged; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; Female; Doxorubicin; Prednisone; senioři; lidé; time to diagnosis; symptoms; Adult; prednison; ženské pohlaví; Male; rituximab; difúzní velkobuněčný B-lymfom; vinkristin; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Cyclophosphamide; Lymphoma, Large B-Cell, Diffuse; Rituximab; Young Adult; senioři nad 80 let; mužské pohlaví; diffuse large B-cell lymphoma; cyklofosfamid